Virtual Temple Project: A historiographical, conceptual and experimental expansion - Viñas Limonchi, Manuel (Street Art & Urban Creativity, 2025)
At the beginning of the present century, the project entitled “Virtual Temple, the paradigm of a new building” (2004) establishes —like an architectural utopia— a theoretical basis and a constructive graphic intervention supported by the continuity of CAD systems and the qualities of user-machine interaction. This article presents an analysis of this project in which narrative, creativity and technology, reviewed in an architectural approach, become the main variables that participate in the development of the objectives, methods, diagnosis and results of the research. Variables and methodologies that determine the morphology and urban location of the building, as well as, inside, the multimedia devices created using industrial design techniques, expressing the style and objectives of the building.